PROFESSIONALIZATION AND HUMAN RESOURCE MANAGEMENT IN COOPERATIVES FROM PARANÁ/BR - Elias Abifadel Monteiro, Rachel; Domingues, Carlos Roberto; Bueno, Janaína Maria (REBRAE, 2017)
With this article we analyzed which strategies of Human Resource Management are used in the process of professionalization of agricultural cooperatives. Using a qualitative approach, with a multiple case study involving three agricultural cooperatives of Paraná, we developed a form based on the study of Miles and Snow (1984) which was answered by eight professionals. As a result, the strategies of the cooperatives towards the process of professionalization were defensive-type, with some features of analysis type and Human Resource Management was partially autonomous. This means that the area played an important role in the process, making the maintenance of employees through training and also in the selection of new talent, but taking into account the requests of managers and not anticipating the demands. It is suggested that the role of Human Resource Management be rethought by the management of agricultural cooperatives, in order to provide more space for participation in planning and strategic decisions